Preclinical safety evaluation of Macleaya Cordata extract: A re-assessment of general toxicity and genotoxicity properties in rodents - Dong, Zhen; Tang, Shu-Sheng; Ma, Xiao-Lan; Li, Chang-Hong; Tang, Zhao-Shan; Yang, Zi-Hui; Zeng, Jian-Guo (Frontiers in Pharmacology, 2022)
Macleaya cordata extract (MCE) is widely used for its diverse pharmacological actions and beneficial effects on farm animals. Modern pharmacological studies have shown that it has anti-inflammatory, anti-cancer, and anti-bacterial activities, and is gradually becoming a long-term additive veterinary drug used to improve animal intestinal health and growth performance. Although some evidence points to the DNA mutagenic potential of sanguinarine (SAN), a major component of MCE, there is a lack of sufficient basic toxicological information on the oral route, posing a potential safety risk for human consumption of food of animal origin. In this study, we assessed the acute oral toxicity, repeated 90-day oral toxicity and 180-day chronic toxicity of MCE in rats and mice and re-evaluated the genotoxicity of MCE using a standard combined in vivo and ex vivo assay. In the oral acute toxicity test, the LD50 for MCE in rats and mice was 1564.55 mg/kg (95% confidence interval 1386.97-1764.95 mg/kg) and 1024.33 mg/kg (95% confidence interval 964.27-1087.30 mg/kg), respectively. The dose range tested had no significant effect on hematology, clinical chemistry, and histopathological findings in rodents in the long-term toxicity assessment. The results of the bacterial reverse mutation, sperm abnormality and micronucleus test showed negative results and lack of mutagenicity and teratogenicity; The results of the rat teratogenicity test showed no significant reproductive or embryotoxicity. The results indicate that MCE was safe in the dose range tested in this preclinical safety assessment. This study provides data to support the further development of maximum residue limits (MRLs) for MCE.